Validity of the International Physical Activity Questionnaire–Short Form for Application in Asian Countries: A Study in Vietnam - Tran, V.; Do, V.; Pham, N.; Nguyen, C.; Tuyet Xuong, N.; Jancey, Jonine; Lee, A. (SAGE Publications, Inc, 2018)
This is the first study in the Asia-Pacific region to examine the criterion validity of the self-reported International Physical Activity Questionnaire–Short form (IPAQ-SF) using accelerometers, in terms of achieving the World Health Organization’s (WHO) recommended physical activity guidelines for health benefits. Vietnamese adults aged 40–65 years (n = 240) wore an ActiGraph GT3X+ accelerometer for at least 5 days and completed the Vietnamese version of the IPAQ-SF. Correlations between IPAQ-SF and accelerometer-measured physical activity intensities varied from.087 to.232. Mean difference in moderate–vigorous physical activity was 0.699 min/day (95% limits: [-107, 109]). Agreement on the classification of achieving the WHO’s physical activity guidelines was 69.16%. The IPAQ-SF identified 71.86% of adults who met the guidelines, whereas 56.09% of those not meeting the guidelines were classified correctly. The IPAQ-SF was found to have acceptable criterion validity and is a useful instrument to classify Vietnamese adults as achieving or not achieving the WHO’s physical activity guidelines for health benefits.